AR-MO Model: Augmented Reality–Based Learning to Enhance Students’ Understanding and Skills in Molecular Geometry - Hani Dewi Ariessanti; Paramadinah Aqil Raditya; Nizirwan Anwar (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study addresses the persistent difficulty Indonesian secondary students face in grasping abstract molecular geometry concepts, exacerbated by the limited adoption of immersive technologies in local curricula. We developed the AR-MO (Augmented Reality-Based Molecular) instructional model using a six-stage Design Science Research (DSR) approach, spanning from problem identification to the communication of results. The model’s effectiveness was evaluated among 349 students across 15 public high schools in Tangerang using a pre-test/post-test design, with data analyzed through descriptive statistics and category-shift mapping. Results indicate a significant enhancement in cognitive understanding, attitudes, and practical skills, with nine schools completely eliminating "Fair" performance categories in favor of "Good" and "Very Good". User satisfaction and usability scores exceeded 90%, confirming the model's acceptance. The novelty of AR-MO lies in its structured integration of 3D visualization within a constructivist framework tailored for the Indonesian secondary education context